USTADZ: GENRE BARU DALAM STRUKTUR BUDAYA MASYARAKAT MADURA - Edi Susanto Edi Susanto (Karsa: Journal of Social and Islamic Culture)
Abstrac This article tries to describe the dynamics of socio-religion of contemporary Madurese society that experience social-cultural diversification and differentiation. Ustadz (muslim teacher) appears the outstanding issue in it. The term of ustadz broadens and develops in meaning. Previously, the terminology of ustadz identified dependent and un-autonomous position. However, this term become more independent and more autonomous in its position currently. This also turns out to be a "competitor" of community which is considered well-established. Moreover, ustadz set themselves as a new genre in cultural structure of contemporary Madurese community. Kata-kata kunci ustadz, masyarakat Madura Kontemporer, diversifikasi, diferensiasi